Copper complexes within the supramolecular solid structure of cyanuric acid and melamine. Issue 11 (1st November 2016) - Dante, Roberto C.; Sánchez-Árevalo, Francisco M.; Chamorro-Posada, Pedro; Vázquez-Cabo, José; Lartundo-Rojas, Luis; Santoyo-Salazar, Jaime; Mendoza-Cruz, Rubén; Velázquez-salazar, J. Jesús; Arellano-Jiménez, M. Josefina; Samaniego, J. Enrique; Solorza-Feria, Omar
ABSTRACT: A complex of copper sulfate was formed by impregnation of the cyanuric acid melamine adduct (CAM) with a solution of copper (II) sulfate. A thermal treatment at 250°C of the dried compound delivered a greenish powder. The UV-Vis spectroscopy showed that an absorption around 700 nm is compatible with a copper (II) sulfate complex coordinated inside the supramolecular structure of CAM. No copper or copper oxide particles were found by means of either transmission or scanning electron microscopy. X-ray photoelectron spectroscopy showed that on the surface there was a considerable amount of Cu(I) (66%) probably coordinated also inside the CAM channels. A brief catalytic test showed the ability of the copper complexes to oxidize sucrose to gluconic acid.